Identifikasi Pengaruh Alasan Ketidakpatuhan terhadap Tingkat Kepatuhan Pasien yang Mengonsumsi Antiretroviral pada Pasien RSUD HIV di Pulau Jawa - Afiv Wahyudi (Universitas Baiturrahim, 2026)
Human Immunodeficiency Virus (HIV) is a virus that infects the body by attacking human white blood cells, causing sufferers to experience a decline in the immune system or a condition of Acquired Immune Deficiency Syndrome (AIDS). Non-compliance is the attitude of patients when they do not follow recommendations or orders maximally in undergoing treatment and is one of the causes of therapy failure. It is necessary to identify the reasons for patient non-compliance as a basis for intervention to improve the level of compliance of HIV patients. This study aims to determine what reasons for non-compliance affect the level of patient compliance so that it can be used as a basis for intervention in an effort to improve the level of compliance in achieving therapy success. This study was conducted with a quantitative approach, observational design and cross-sectional research type. The study was conducted at a Regional General Hospital in Java on adult HIV patients diagnosed with HIV, receiving first-line ARVs, complete medical record data, willing to be interviewed and not lost to follow-up. Univariate analysis was performed using Microsoft Excel software application and continued with bivariate statistical analysis using IBM SPSS statistic 22 application. To see the influence of each reason for non-compliance on the level of compliance, the analysis was performed using binary logistic regression bivariate test. The results showed that patient age characteristics had an effect on compliance (P = 0.017 or <0.05) OR of 3.104 times, 95% CI (1.225-7.867) on compliance. Of the 17 measurements of reasons for non-compliance, the reason for wanting to avoid side effects had an effect on the level of compliance (P = 0.048) and could affect compliance OR of 0.384 times, 95% CI (0.149-0.990) so that age factors and factors wanting to avoid side effects need to be considered in conducting interventions for HIV patients.